A biomechanical study of the takeoff preparation and the takeoff motions in elite male long jumpers - Shimizu, Y.; Ae, M.; Koyama, H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare the takeoff preparation and the takeoff motions of the world level and Japanese long jumpers by using the method of the standard motion. The subjects were nine World jumpers (World group) and ten Japanese jumpers (Japan group). The motion from the second-last stride to the takeoff was videotaped by two high-speed VTR cameras. The standard motions of World and Japan group were established by using the method of Ae et al. (2007). The results were summarized as follows; 1) The World group indicated the greater horizontal CG velocity and smaller decrease in the horizontal CG velocity during the takeoff preparation and takeoff than those of the Japan group. 2) The Japan group tended to flex and extend the knee joint of the support leg, and to raise the trunk in earlier timing during the preparation phase.